أثر التحول الرقمي على التنمية المستدامة في الجزائر دراسة قياسية (1990 -2020) - الأسود، محمد; منصوري، عبد الوهاب; قديري، سمير (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى إيجاد العلاقة بين التحول الرقمي المعبر عنه بمتغيرات تمثلت في الأفراد الذين يستخدمون الإنترنت من السكان، واشتراكات الأفراد بالهاتف المحمول والثابت، مع التنمية المستدامة المعبر عنها بنصيب الفرد من الناتج المحلي الإجمالي في الجزائر للفترة من 1990 إلى 2020، وقد استخدمت الدراسة لهذا الغرض المنهج الوصفي والتحليلي، مع استخدم برمجية EViews10 لقياس العلاقة بين المتغيرات. خلص الدراسة إلى وجود علاقة إيجابية في الأجل القصير بين معلمة نسبة الأفراد من السكان الذين يستخدمون الإنترنت INUSINT والتنمية المستدامة GDPPCKN حيث بلغت قيمة المعلمة 0.003375 بقيمة احتمالية 0.0015 أي أقل من مستوى معنوية 1%، أما في الأجل الطويل ثبت وجود علاقة إيجابية بين معلمة اشتراكات الهاتف المحمول LMOCESU والتنمية المستدامة، حيث أن بلغت قيمة المعلمة 0.0444 بقيمة احتمالية 0.0000 أي أقل من مستوى معنوية 1%، وهو ما توافق النظرية الاقتصادية. Abstract: This study aims to find the relationship between digital transformation expressed by variables represented by individuals using the Internet from the population, and individual subscriptions to mobile and fixed phones, with sustainable development expressed by the gross domestic product per capita in Algeria for the period from 1990 to 2020. The study used the descriptive and analytical approach for this purpose, with the use of EViews10 software to measure the relationship between the variables. The study concluded that there is a positive relationship in the short term between the parameter of the percentage of individuals from the population using the Internet INUSINT and sustainable development GDPPCKN, where the value of the parameter reached 0.003375 with a probability value of 0.0015, that is less than a significance level of 1%. As for the long term, a positive relationship was proven between the parameter of mobile phone subscriptions LMOCESU and sustainable development, where the value of the parameter reached 0.0444 with a probability value of 0.0000, that is less than a significance level of 1%, which is consistent with economic theory.
مداخلة
Keywords: تحول رقمي; تنمية مستدامة; منهجية ARDL; Digital transformation; sustainable development; ARDL Model